Urolithin A Prevents Focal Cerebral Ischemic Injury via Attenuating Apoptosis and Neuroinflammation in Mice. (10th November 2020) - Lin, Xiao-Hong; Ye, Xiu-Juan; Li, Qing-Feng; Gong, Zhuo; Cao, Xin; Li, Jian-Hua; Zhao, Shen-Ting; Sun, Xiang-Dong; He, Xiao-Song; Xuan, Ai-Guo
Highlights: Urolithin A reduces neuron loss and promoted neurogenesis after ischemic stroke. Urolithin A attenuates apoptosis by regulating apoptotic-related proteins. Urolithin A treatment inhibits glial activation via affecting inflammatory signaling pathways. Urolithin A ameliorates infarction, neurological deficit scores, and spatial memory deficits. Abstract: Neuroinflammation contributes to neuronal death in cerebral ischemia. Urolithin A (UA), a gut microbial metabolite of ellagic acid, has emerged as a potential anti-inflammatory agent. However, its roles and precise mechanisms in stroke remain unknown. Here we found that UA treatment ameliorated infarction, neurological deficit scores, and spatial memory deficits after cerebral ischemia. Furthermore, UA significantly reduced neuron loss and promoted neurogenesis after ischemic stroke. We also found that UA attenuated apoptosis by regulating apoptotic-related proteins. Meanwhile, UA treatment inhibited glial activation via affecting inflammatory signaling pathways, specifically by enhancing cerebral AMPK and IκBa activation while decreasing the activation of Akt, P65NFκB, ERK, JNK, and P38MAPK. Our findings reveal a key role of UA against ischemic stroke through modulating apoptosis and neuroinflammation in mice.